The Provision of Private Healthcare Services in European Countries: Recent Data and Lessons for Universal Health Coverage in Other Settings - Montagu, Dominic (Frontiers in Public Health, 2021)
Universal Health Coverage (UHC) exists in all of the countries of Europe, despite variation on the ownership structure of health delivery systems. As countries around the world seek to advance UHC and manage the private sector within their health systems, the European experiences can offer useful insights. We found four different models for the provision of healthcare, with the private sector predominant in some countries, and of minimal importance in others. The European experiences indicate that UHC can be effectively provided with, or without, large-scale private sector provision in hospital, specialty, and primary care services, and that moreover it can be provided with high levels of patient satisfaction. These findings offer regulatory models for countries in other regions to review as they advance UHC.